Pengaruh Kepuasan Kerja Terhadap Kinerja Pegawai Kejaksaan Negeri Berau - Happy Adianita; Dados Susilowati; Retno Muslinawati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to determine the effect of job satisfaction on the performance of the Berau District Prosecutor. Where the independent variable of job satisfaction consist of the work it self and co-workers. The research design used is quantitave descriptive associative. The method of data collection is using a distributed questionnaire. The sampling technique uses a saturated sample where all members of the population are sampled. The sampled used in this study amounted of 30. The results showed that the work variable it self and co-workers simultaneously and partially had a positive and significant influence on employee performance. From the results of the two independent variables which are the dominant variables affecting the performance of the Berau District Prosecutor, the work variable is proven by the largest regression coefficient value, which is 0.472 compared to the regression coefficients of other variables